Paternal Y chromosomal genotyping reveals multiple large-scale admixtures in the formation of Lolo-Burmese-speaking populations in southwest China - Jianxin Guo; Bingying Xu; Lanjiang Li; Guanglin He; Han Zhang; Hui-Zhen Cheng; Jinxing Ba; Xiaomin Yang; Lanhai Wei; Rong Hu; Chuan-Chao Wang (Taylor & Francis Group, 2019)
Background: Bai and Yi people are two Tibeto-Burman speaking ethnic groups in Yunnan, southwest China. The genetic structure and history of these two groups are largely unknown due to a lack of available genetic data. Aim: To investigate the paternal genetic structure and population relationship of the Yi and Bai people. Subjects and methods: We collected samples from 278 Bai individuals and 283 Yi individuals from Yunnan and subsequently genotyped 43 phylogenetically relevant Y-SNPs in those samples. We estimated haplogroup frequencies and merged our data with a reference database including 46 representative worldwide populations to infer genetic relationships. Results: Y chromosomal haplogroup O-M175 is the dominant lineage in both Bai and Yi people. The Bai and Yi show a close genetic relationship with other Tibeto-Burman-speaking populations with high frequencies of haplogroup O2a2b1a1-Page23, which is also confirmed by PCA. The frequencies of the Tai-Kadai specific lineage O1a-M119, the southern China widespread lineage O1b-P31 and the eastern China enriched lineage O2a1b-002611, are also relatively high in our studied populations. Conclusions: The paternal Y chromosomal affinity of the Bai and Yi with Tibeto-Burman groups is consistent with the language classification. During the formation of the Bai and Yi populations, there were multiple large-scale admixtures, including the expansion of Neolithic farming populations from northern China, the assimilation of Tai-Kadai-speaking populations in southwest China, the demographic expansion driven by Neolithic agricultural revolution from southern China, and the admixture with populations of military immigration from northern and eastern China.